Exploring the use of the concept human dignity in disability human rights law: from UNCRPD to EctHR - Elif CELIK (Age of Human Rights Journal, 2021)
The UN Convention on the Rights of Persons with Disabilities (CRPD) accommodates the concept of human dignity more fully than does any other human rights treaty. The role and interpretation of dignity is thus particularly interesting from the perspective of disability human rights and case law. This study examines the role and significance of the concept of dignity in relation to the human rights disability discourse and jurisdiction through the guidance and impact of the CRPD. It examines the currently available jurisprudence of the CRPD Committee and the European Court of Human Rights (ECtHR) in light of the CRPD, seeking to identify the rights that are particularly related to the concept of dignity through the perspective of disability and to identify the requirements of the respect for dignity for persons with disabilities. While accepting the limitations of the sources in this examination due to the recent history of the CRPD, the study nevertheless locates some points where human dignity has particular relevance to the realisation of the rights protected in the CRPD.